2007
DOI: 10.1007/s00442-007-0748-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in a complex world: interactive effects of food and temperature on fitness components of a seed beetle

Abstract: Most studies of phenotypic plasticity investigate the effects of an individual environmental factor on organism phenotypes. However, organisms exist in an ecologically complex world where multiple environmental factors can interact to affect growth, development and life histories. Here, using a multifactorial experimental design, we examine the separate and interactive effects of two environmental factors, rearing host species (Vigna radiata, Vigna angularis and Vigna unguiculata) and temperature (20, 25, 30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 73 publications
7
110
0
6
Order By: Relevance
“…Karl & Fisher 2008), but where interactive effects of diet and temperature upon growth have been investigated, consideration of body temperature preference and nutrient utilization were not the focus (e.g. Stillwell et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Karl & Fisher 2008), but where interactive effects of diet and temperature upon growth have been investigated, consideration of body temperature preference and nutrient utilization were not the focus (e.g. Stillwell et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of plasticity studies and studies that have tested for sex differences in plasticity in body size have examined environmental variables independently of one another. Nevertheless, recent studies have shown that multiple environmental variables can interact, producing complex patterns of plasticity (Sultan et al 1998;Sultan 2001;Relyea 2004;Relyea & Auld 2005;Stillwell et al 2007b;Diamond & Kingsolver 2010). In addition, interactions between environmental variables can have different effects on the sexes, producing complexity in sex differences in plasticity in size and hence affecting patterns of SSD (De Block & Stoks 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, interactions produced by ANOVA can be misleading when the proportional or relative effects (i.e. ratios such as female/male size) are of interest because ANOVA tests for interactions by measuring linear differences between treatment means (Stanton & Thiede 2005;Stillwell et al 2007b;Fraker & Peacor 2008). In other words, when there is a large effect of one variable on the overall mean, linear differences do not translate into proportional changes.…”
Section: (D) Measurement Of Physiological Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…All offspring developed at 25°C and 15:9 light:dark in a single growth chamber. We used mung bean as the rearing host because larval survivorship is high on this host for both the SI and BF populations (Stillwell et al 2007). The positions of dishes in the chamber were rotated daily.…”
Section: Line Cross Experimental Designmentioning
confidence: 99%